2021
DOI: 10.1126/sciadv.abd6162
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy ordering induced topological electronic transition in bulk Eu 2 ZnSb 2

Abstract: Metal-semiconductor transitions from changes in edge chirality from zigzag to armchair were observed in many nanoribbon materials, especially those based on honeycomb lattices. Here, this is generalized to bulk complex Zintl semiconductors, exemplified by Eu2ZnSb2 where the Zn vacancy ordering plays an essential role. Five Eu2ZnSb2 structural models are proposed to guide transmission electron microscopy imaging. Zigzag vacancy ordering models show clear metallicity, while the armchair models are semiconducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Very recently, this has been further demonstrated that these materials host nontrivial topological phases . For instance, by changing the cation ordering in Zintl phase bulk Eu 2 ZnSb 2 , a topological transition was observed, demonstrating its tunabilty …”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Very recently, this has been further demonstrated that these materials host nontrivial topological phases . For instance, by changing the cation ordering in Zintl phase bulk Eu 2 ZnSb 2 , a topological transition was observed, demonstrating its tunabilty …”
Section: Introductionmentioning
confidence: 89%
“…44 Very recently, this has been further demonstrated that these materials host nontrivial topological phases. 45 For instance, by changing the cation ordering in Zintl phase bulk Eu 2 ZnSb 2 , a topological transition was observed, demonstrating its tunabilty. 45 Although numerous studies have already been devoted to Zintl phase compounds, especially in the field of thermoelectric materials, 43,46,47 studies on the topological properties of monolayer Zintl phase A 2 MX 2 have yet to be fully explored.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that locally ordered zinc atoms retain the material’s high electronic conductivity, while long-range disorder keeps the thermal conductivity low. “We knew that the key feature of Eu 2 ZnSb 2 is a crystal structure that has a Zn-site with a 50% occupancy 3 ,” says Zhang, “but the exact crystal model is actually unknown so the high degree of local order was an unexpected find.”…”
mentioning
confidence: 99%